Aerodynamic admittance of a 5:1 rectangular cylinder in turbulent flow. Issue 189 (June 2019) - Yang, Yang; Li, Mingshui; Su, Yi; Sun, Yanguo
Abstract: It is known for some time that the buffeting force acting on a structure induced by turbulent flow is intrinsically three-dimensional. To understand the influence of the three-dimensional effects fundamentally, clarifications are made regarding the relations between the one-wavenumber aerodynamic admittance, the two-wavenumber aerodynamic admittance and the generalized aerodynamic admittance. Then via wind tunnel tests, these three lift aerodynamic admittances of a 5:1 rectangular cylinder in grid turbulence are identified. An empirical formula for determining the one-wavenumber aerodynamic admittance of a 5:1 rectangular cylinder is proposed based on the experimental data and analysis. In this process, an empirical model for the spanwise influence term and an adapted form of the lift coherence function are used, which enable the use of the measured lift coherence for the estimation of the spanwise influence term. Based on these results, this work indicates that the generalized aerodynamic admittance, which is usually used in the practical engineering, is the combined results of the one-wavenumber aerodynamic admittance and the three-dimensionality effects. The influence of the three-dimensionality effects can be integrally considered by a 3D effects factor, the generalized aerodynamic admittance can be therefore expressed as the product of the one-wavenumber aerodynamic admittance and the 3D effects factor. It is then further revealed that the 3D effects factor is less than 1 and depends on the ratio of the turbulence integral scale to the chord, which makes the generalized aerodynamic admittance being smaller than the one-wavenumber aerodynamic admittance and being flow field-dependent. Highlights: Clarifications are made regarding three concepts of aerodynamic admittances. Lift aerodynamic admittances of a 5:1 rectangular cylinder are identified. An reasonable explanation of the generalized aerodynamic admittance is given.